Gainesville's Urban Forest Canopy Cover - Francisco Escobedo; Jennifer A. Seitz; Wayne Zipperer (EDIS)
FOR-215, a 3-page illustrated fact sheet by Francisco Escobedo, Jennifer A. Seitz, and Wayne Zipperer, examines how tree cover changes over time, how tree composition and location influence urban forest canopy and leaf area, and how tree and ground surface covers vary across Gainesville. Includes references. Published by the UF School of Forest Resources and Conservation, March 2009.